COLLEGE ENTRANCE TESTS AND ACCOUNTING GRADES. - Brown, Robert O. (The Accounting Review, 1964)
Abstract The article focuses on college entrance tests and accounting grades. A case for standardized college entrance test is discussed. Some years ago as manager of an office, the author was much troubled by female employee turnover. The personnel manager and the author concluded that aptitude-interest testing would be the answer to the problem and accordingly adopted a battery of tests for prospective employees. In looking over the test results for a group of applicants, one girl seemed to be outstanding. The girl's interest test rated high; she appeared to be emotionally stable; her aptitude test was good; she was intelligent enough, but not too intelligent. Admittedly standardized tests have become increasingly popular, in spite of the lack of conclusive validation data and unlimited criticism. It is said that the trend of the use of tests is an argument for educators. The opinion has been expressed that educators would not have accepted them unless they had proven themselves, which proves that many educators don't know educators. In the accounting field there are interest, aptitude and progress tests published and evaluated by the American Institute of Accountants.